Philosophy of modern bioengineering - Shogar, Ibrahim; Abdul Rahman, Suzanah (IIUM Press, International Islamic University Malaysia, 2017)
This article investigates the philosophical foundations of modern bioengineering to articulate its rational framework. Engineering as an ultimate mechanism to transform knowledge into practice is essential for both physical and biological sciences. It reduces data, concepts, and designs to pictorial forms. Integration of engineering with newly emerging biosciences, has presented a unique opportunity to overcome the major challenges that faced by environmental ecology and human health. To harness potentials of modern bioengineering and establish a sustainable foundation for green technology, scientists and engineers should be acquainted with the normative questions of science and technology. Beside acquiring the general principles of scientific research and identification of the intrinsic goals of the endeavour, philosophy of bioengineering exposes scientists to both the descriptive ‘how’ questions of the physical world as well as the normative ‘why’ questions of values. Such an interdisciplinary approach is essential, not only for inspiration to acquire the genuine knowledge, but also to expose the scientists and bioengineers to their ethical and social responsibilities. Introducing the conceptual framework of bioengineering, this paper has investigated the three major philosophies that have been dominating the basic presuppositions of scientific research method in modern history of science, namely: (i) the mechanical approach of physical sciences, (ii) the functional (goal-guided) approach of biological processes, and (iii) the integrated approach. The paper also has conducted an analytical study on various branches of the emerging discipline of bioscience. The paper has concluded that adopting the interdisciplinary approach is essential to harness potentials of bioengineering and to establish foundations of green technology based on moral values. To materialize such a noble goal, both the epistemological and normative knowledge must be acquired in bioengineering research and education. The former is essential for invention and innovation; meanwhile the later exposes bioengineers to their ethical and moral commitments.